Everything you wanted to know about Indians but were afraid to ask - Treuer, Anton (Minnesota Historical Society Press, 2023)
"What have you always wanted to know about Indians? Do you feel like you should already know the answers--or are concerned that your questions may be offensive? For more than a decade, Anton Treuer's clear, candid, and informative book has answered questions for tens of thousands of readers. This revised edition both revisits old questions from a new perspective and expands on topics that have become increasingly relevant over the past decade, including activism and tribal enrollment; truth and reconciliation efforts; gender roles and identities in Indigenous communities; the status of Alaskan Natives and Canadian First Nations; and much more."--